Intentions to Use Emergency Contraception: The Role of Accurate Knowledge and Information Source Credibility. Issue 4 (4th July 2018) - Garrett Wagner, Kyla P.; Widman, Laura; Nesi, Jacqueline; Noar, Seth M.
ABSTRACT: Background : Emergency contraception (EC) is a highly effective form of birth control that may lower rates of unintended pregnancy among young women. But efforts to disseminate EC to women are hampered by misinformation and inadequate information.Purpose : The purpose of this study was to determine the sources from which young women learn about EC (including health care providers, friends/interpersonal sources, media sources, or no information sources) and to examine associations between source credibility with the accuracy of EC knowledge and intentions to use EC.Method : Using a computer-based survey, 339 college women (M age = 18.4) reported their EC information sources, knowledge about EC, and behavioral intentions to use EC.Results : In total, 97% of participants had heard of EC from at least one source and 49% indicated that they were highly likely to use EC in the future if needed. Results demonstrated that EC knowledge mediated the relationship between EC information source credibility and intentions to use EC.Discussion : This study contributes important insights to a scarce literature on EC information sources and the factors that predict intentions to use EC.Translation to Health Education Practice : Future EC promotion efforts should target Health Education sources instead of media or interpersonal sources to promote EC knowledge and use among young sexually at-risk populations.